ANALISIS PERUBAHAN PENGGUNAAN LAHAN TERHADAP TINGKAT KERENTANAN KEKERINGAN DI DAS ANTOKAN - Aldhy Rahman Fajar; Ahyuni Ahyuni (DEPARTEMEN GEOGRAFI FIS UNP, 2026)
Changes in land use in the Antokan watershed are land that has been built into a built area that requires active planning, land use changes are unavoidable in a regional development process. In the Antokan watershed, careful planning is needed in building land use to prevent the worst possible occurrence, one of which is by making a land use planning model to control drought in the Antokan watershed, the analysis used in this study is the supervised classification in calculating changes land use and SWAT models and the SMDI index to determine the level of drought vulnerability in the Antokan watershed. Based on the research results on land use changes, the Antokan watershed in 2011-2021 experienced significant changes in the use of secondary forest land with an area of 14603.3 ha. The vulnerability to drought in the Antokan watershed in 2011 with no drought vulnerability increased in 2021 with sub-watersheds 15, 17, 21, 24, 34, 36, 40, and 43 being “Very Vulnerable”.